On the Use of Semi-empirical Flame Models for Spreading Chaparral Crown Fire - Cobian-Iñiguez, Jeanette; Aminfar, AmirHessam; Weise, David R.; Princevac, Marko (Frontiers in Mechanical Engineering, 2019)
Flame geometry plays a key role in shaping fire behavior as it can influence flame spread, radiative heat transfer and fire intensity. For wildland fire, a thorough understanding of relationships between flame geometry including flame length, flame height and flame tilt can help advance the derivation of comprehensive models of wildfire behavior. Within the fire community, a classical flame modeling approach has been the development of semi-empirical models. Many of these models have been derived for surface fuels or for pool fire configurations. However, few have sought to model flame behavior in chaparral crown fires. Thus, the objective of this study was to assess the applicability of existing semi-empirical models on observed chaparral crown fire geometry. Semi-empirical models of flame tilt, flame height and flame length were considered. Comparison with experimental observation of crown fuel layer flame height showed good agreement between two-fifths power law that relates flame height to heat release rate. Predictions of flame tilt were obtained from application of semi-empirical power-law correlations relating flame tilt angle to Froude number. Observed flame tilt values exhibited low correlation with predicted values. Thus, two new power-law correlations were proposed. Coefficients for new models were obtained from regression analysis.